Aspek Kelisanan dalam Naskah “Hikayat Raja-Raja Siam” - Khofifah Tri Lestari (Balai Bahasa Provinsi Riau, 2022)
The purpose of this study was to elaborate the oral aspects contained in Hikayat Raja-Raja Siam based on Walter J. Ong’s orality theory . The object of this research is the text of Hikayat Raja-Raja Siam from collections of Leiden University. This study used descriptive qualitative method . The researcher read carefully the literary work before analyzingit based on Walter J. Ong’s orality theory . The results of this study show that there are four aspects of orality in Hikayat Raja-Raja Siam. They are conservative or traditional, exaggerative or elaborate, additive, and participatory forms. Moreover, this study shows that Hikayat Raja-Raja Siam also tries to reveal the uniqueness of traditionality in Malay literature. The existence of a written tradition does not necessarily make the oral tradition disappear, instead the author then uses the residue of the oral culture as an aesthetic in his work.